2018
DOI: 10.1002/2211-5463.12392
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofDNAmethyltransferase leads to increased genomic 5‐hydroxymethylcytosine levels in hematopoietic cells

Abstract: 5‐Hydroxymethylcytosine (5hmC) is produced from 5‐methylcytosine (5mC) by Ten‐eleven translocation (TET) dioxygenases. The epigenetic modification 5hmC has crucial roles in both cellular development and differentiation. The 5hmC level is particularly high in the brain. While 5mC is generally associated with gene silencing/reduced expression, 5hmC is a more permissive epigenetic mark. To understand its physiological function, an easy and accurate quantification method is required. Here, we have developed a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Furthermore, we demonstrate that losses of 5mC within the SPRY2 promoter inversely correlate with increased promoter 5hmC. Indeed, the phenomenon of global epigenetic dysregulation, linking decreased levels of 5mC with increased levels of 5hmC, has been observed in pontine gliomas and hematopoietic cells [44,45]. In other cases, global losses of 5hmC have been linked to increases in intragenic 5mC and subsequently decreased expression of tumor suppressor genes as reported in kidney cancer [46].…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, we demonstrate that losses of 5mC within the SPRY2 promoter inversely correlate with increased promoter 5hmC. Indeed, the phenomenon of global epigenetic dysregulation, linking decreased levels of 5mC with increased levels of 5hmC, has been observed in pontine gliomas and hematopoietic cells [44,45]. In other cases, global losses of 5hmC have been linked to increases in intragenic 5mC and subsequently decreased expression of tumor suppressor genes as reported in kidney cancer [46].…”
Section: Discussionsupporting
confidence: 62%
“…For combinations therapies, clinical studies should be planned taking into account the different molecular mechanisms involved in vitamin C antitumor activity that can be observed even at lower concentrations, such as induction of DNA demethylation [ 167 , 195 , 196 ]. In particular, the conversion of 5mC to 5hmC deriving from vitamin C-mediated activation of TETs may synergize with passive DNA demethylation (i.e., absence of methylation of newly synthesized DNA strands) obtained by azacytidine or decitabine that are inhibitors of DNMT1 [ 197 , 198 , 199 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that Aza could also increase transgene expression levels, stability, and the retention of transgene regardless of selection pressures, which are consistent with the previous studies . As a cytidine analogue, Aza can reduce the methylation level by covalently binding with DNA methyltransferase to decrease the biological activity of DNA methyltransferase . In the previous study, cells were treated by a daily dose of 4 μM of Aza for 3 days and lost productivity was partially restored .…”
Section: Discussionmentioning
confidence: 99%
“…19 As a cytidine analogue, Aza can reduce the methylation level by covalently binding with DNA methyltransferase to decrease the biological activity of DNA methyltransferase. 34,35 In the previous study, cells were treated by a daily dose of 4 μM of Aza for 3 days and lost productivity was partially restored. 19 However, in our present study, the cytotoxicity of 4 µM Aza concentration is too high to kill the most of the CHO cells, 1 μM of Aza had no significant influence on cell density and viability of stably transfected CHO cells cultured for 60 generations (data not shown).…”
Section: Discussionmentioning
confidence: 99%